New insights into the variability of reproduction modes in European populations of Rubus subgen. Rubus: how sexual are polyploid brambles? - Šarhanová, Petra; Vašut, Radim J; Dančák, Martin; Bureš, Petr; Trávníček, Bohumil (Sexual plant reproduction, 2012)
Rubus subgen. Rubus includes common European species with highly complicated taxonomy, ongoing hybridisation and facultative apomixis. Out of approximately 750 species recognised in Europe, only 3 diploid sexual species are known, along with numerous apomictic brambles that are highly connected to polyploidy. One exception of a tetraploid taxon is R. ser. Glandulosi, which is known for prevalent sexuality. This taxon highly hybridises with tetraploid members of R. ser. Discolores and leads to the origin of many hybridogenous populations and individuals. In this study, we verify reproduction modes in different diploid, triploid and tetraploid species of subgen. Rubus, with focus on taxa putatively involved in such hybridisation by applying flow cytometric seed screen analysis. We found 100 % sexuality of diploid species, whereas triploid species had obligate unreduced embryo sac development. In contrast, tetraploid plants had varying degrees of sexuality. Additionally, we discovered that R. bifrons has the ability to undergo a reproduction mode switch as a reaction to environmental conditions. These results provide insight into reproductive modes of European brambles and shed light on their reticulate evolution and speciation.
Keywords: semena rostlinná; Genome Size; druhová specificita; Apomixis; délka genomu; zeměpis; Endosperm; Reproduction; endosperm; Rosaceae; Geography; Seeds; Species Specificity; Flow Cytometry; rozmnožování; partenogeneze; průtoková cytometrie; apomixie; tetraploidie; Diploidy; Parthenogenesis; Polyploidy; Tetraploidy; diploidie; polyploidie